Prevalence of condensing osteitis on panoramic radiographic at the Department of Radiology RSGMP Hasanuddin University in 2023: Prevalensi condensing osteitis pada radiografi panoramik di Departemen Radiologi RSGMP Universitas Hasanuddin Tahun 2023 - Musmar, Aisyah; Yunus, Barunawaty (Makassar Dental Journal PDGI Makassar, 2024)
The most common radiopaque lesion in the jaws is condensing osteitis (CO), which occurs in 4-7% of the general population. The hallmark of CO consists of a solid radiopaque mass adjacent to the apex of the tooth and has well-defined edges and a faint tran-sition to the surrounding bone. This study examined the prevalence of CO on panoramic radiographs at the Radiology Department of Dental Hospital Hasanuddin University in 2023. Descriptive observational study with cross-sectional design through panoramic radiography data in January-December, then the results were entered into distribution tables. The CO was mostly found at the age of 21-30 years as much as 33.0%, with female gender as much as 62.1%, and in the lower jaw as much as 72.8%. It was concluded that the prevalence of CO in the oral cavity was high due to the low level of knowledge and public awareness of oral health maintenance and suboptimal oral health services.